2017
DOI: 10.1111/bcp.13457
|View full text |Cite
|
Sign up to set email alerts
|

QTc prolongation during ciprofloxacin and fluconazole combination therapy: prevalence and associated risk factors

Abstract: The prevalence of QTc prolongation in patients using ciprofloxacin and fluconazole is low compared with the prevalence in the general population, which varies from 5% to 11%. In addition, no risk factors were found. Given the low prevalence, routine ECG monitoring in patients on this therapy should be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 42 publications
1
22
1
1
Order By: Relevance
“…Several lines of evidence indicate that a great number of DDIs may often occur by two or more mechanisms acting in concert [29], which makes the prediction of DDIs in patients treated with CDK4/6 inhibitors more complex. For example, combination of fluoroquinolones and azoles can be used as prophylaxis or treatment of infections in neutropenic cancer patients [55]. Unfortunately, many of these drugs have QTc prolonging potential [55] and the use of this combination should be avoided in at-risk patients for long QT syndrome, including those receiving ribociclib.…”
Section: Complex Ddismentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence indicate that a great number of DDIs may often occur by two or more mechanisms acting in concert [29], which makes the prediction of DDIs in patients treated with CDK4/6 inhibitors more complex. For example, combination of fluoroquinolones and azoles can be used as prophylaxis or treatment of infections in neutropenic cancer patients [55]. Unfortunately, many of these drugs have QTc prolonging potential [55] and the use of this combination should be avoided in at-risk patients for long QT syndrome, including those receiving ribociclib.…”
Section: Complex Ddismentioning
confidence: 99%
“…For example, combination of fluoroquinolones and azoles can be used as prophylaxis or treatment of infections in neutropenic cancer patients [55]. Unfortunately, many of these drugs have QTc prolonging potential [55] and the use of this combination should be avoided in at-risk patients for long QT syndrome, including those receiving ribociclib. Beside representing an additional risk factor for QT prolongation per se, the torsadogenic potential of ribociclib may be further increased as a consequence of azole-mediated CYP3A4 inhibition.…”
Section: Complex Ddismentioning
confidence: 99%
“…Such interactions are commonly found as case reports, as it is unethical to design studies to confirm these serious risks in clinical studies. However, for some DDIs it is possible to study the clinical manifestation of a potential DDI in an observational study using real-world drug utilization data 202 . Secondly, selection of the ABs included in this review was based on their frequent use in COPD and therefore information for other ABs used for COPD comorbidities, such as atypical Mycobacterium spp., is limited, and this may restrict the scope of application of this review.…”
Section: Discussionmentioning
confidence: 99%
“…As the prevalence of QTc prolongation in patients varies from 5% to 11% [ 33 ], based on previously published data which has confirmed that the prolonged QTc interval is a predictor of cardiovascular events [ 19 , 20 , 21 ], we decided to avoid administering any drug influencing the extension of the QTc interval. Due to the increasing rate of resistance to fluoroquinolones and their potential negative effect on ECG alterations, we introduced the prophylaxis of UTI with fosfomycine tromethamine [ 33 , 34 ]. Such a strategy enabled the exclusion of the potential negative influence of antibiotic prophylaxis on ECG, and could be more effective in the context of UTI prevention.…”
Section: Discussionmentioning
confidence: 99%